Native speakers aren't perfect': Japanese English learners' identity transformation as English users. (November 2022) - Sakamoto, Mitsuyo; Furukawa, Gavin
Abstract: This case study explores two Japanese college English majors' second language identity formation in becoming confident English users via notions of adequation/distinction, authentication/denaturalization and authorization/illegitimation (Bucholtz & Hall, 2005). The study is particularly unique in that perspectives of not one but two instructors teaching the same students were brought together in identifying these three dimensions of their students. Data were collected predominantly from an end-of-the year online interview, triangulated with other sources including questionnaires, writing samples, and reflection papers in the course of one academic year. The analysis revealed how Japanese students can easily succumb to public mainstream hegemonic discourse in which returnee students (those with prolonged sojourn abroad) are glorified compared to those educated in Japan. The two students displayed such ideologies at the beginning of the year but then their identity transformed, gaining more confidence and improving their English skills. The major reasons that the students attributed for the shift were 1) exposure to returnee students; 2) exposure to other non-native English speakers; 3) creation of amicable class atmosphere, and surprisingly 4) demanding course content. The study illuminates how hegemonic language ideologies can be challenged in an EFL classroom.